GAP-a-Farm: A tool to support GAP compliance and information based decision making in horticulture - Fernández, Alejandro (2025)
Adoption of information technology in horticulture is low, especially in developing countries. Governments across the world issue new regulation to govern the application of good agricultural practices affecting production, storage and selling activities, while certification program require that farmers keep detailed records of farm events, for auditing purposes. These changes in the context of horticultural practices, represent an opportunity to test whether a compliance and decision support systems can shift farmers processes to utilize technology incorporating data and expert advice. GAP-a-Farm is a tool to ease record keeping, and to turn recorded data into alerts and advice. This chapter documents the key aspects of the system’s design, and reports on preliminary discussions with end-users that take part in a pilot study in Argentina.